The effects of cold environments on double-poling performance and economy in male Cross-Country Skiers Wearing a Standard Racing Suit - Wiggen, Ø. N.; Heidelberg, C. T.; Waagaard, S. H.; Færevik, H.; Sandbakk, O. (International Journal of Sports Physiology and Performance, 2016)
Purpose: